A Potential Role for Endogenous Glucagon in Preventing Post-Bariatric Hypoglycemia - Lobato, Carolina B.; Pereira, Sofia S.; Guimarães, Marta; Hartmann, Bolette; Wewer Albrechtsen, Nicolai J.; Hilsted, Linda; Holst, Jens J.; Nora, Mário; Monteiro, Mariana P. (Frontiers in Endocrinology, 2020)
Obesity and obesity-related diseases are major public health concerns that have been exponentially growing in the last decades. Bariatric surgery is an effective long-term treatment to achieve weight loss and obesity comorbidity remission. Post-bariatric hypoglycemia (PBH) is a late complication of bariatric surgery most commonly reported after Roux-en-Y gastric bypass (RYGB). PBH is the end result of postprandial hyperinsulinemia but additional endocrine mechanisms involved are still under debate. Our aim was to characterize entero-pancreatic hormone dynamics associated with postprandial hypoglycemia after RYGB. Individuals previously submitted to RYGB (N=23) in a single tertiary hospital presenting PBH symptoms (Sym, n=14) and asymptomatic weight-matched controls (Asy, n=9) were enrolled. Participants underwent a mixed-meal tolerance test (MMTT) to assess glucose, total amino acids (total AA), insulin, C-peptide, glucagon, glucose-dependent insulinotropic polypeptide (GIP), glucagon-like peptide-1 (GLP-1) and neurotensin (NT). We found that hypoglycemia during the MMTT was equally frequent in Sym and Asy groups (p=1.000). Re-grouped according to glucose nadir during the MMTT (Hypo n=11 vs NoHypo n=12; nadir <3.05mmol/l vs ≥3.05mmol/l), subjects presented no differences in anthropometric (BMI: p=0.527) or metabolic features (HbA1c: p=0.358), yet distinct meal-elicited hormone dynamics were identified. Postprandial glucose excursion and peak glucose levels were similar (p>0.05), despite distinct late glycemic outcomes (t=60 min and t=90min: p<0.01), with overall greater glycemic variability in Hypo group (minimum-to-maximum glucose ratio: p<0.001). Hypo group meal-triggered hormone profile was characterized by lower early glucagon (t=15 min: p<0.01) and higher insulin (t=30 min: p<0.05, t=45 min: p<0.001), C-peptide (t=30 min: p<0.01, t=45 min: p<0.001, t=60 min: p<0.05) and GLP-1 (t=45 min: p<0.05) levels. Hyperinsulinemia was an independent risk factor for hypoglycemia (p<0.05). After adjusting for hyperinsulinemia, early glucagon correlated with glycemic nadir (p<0.01) and prevented postprandial hypoglycemia (p<0.05). A higher insulin to glucagon balance in Hypo was observed (p<0.05). No differences were observed in total AA, GIP or NT excursions (p>0.05). In sum, after RYGB, postprandial hyperinsulinemia is key in triggering PBH, but a parallel and earlier rise in endogenous glucagon might sustain the inter-individual variability in glycemic outcome beyond the effect of hyperinsulinism, advocating a potential pivotal role for glucagon in preventing hyperinsulinemic hypoglycemia.